Knowledge management practice in private sector: building the way for Saudi Arabia strategic growth and transformation to knowledge-based economy - Gharamah, Abdulrahman; Noordin, Mohamad Fauzan; Imtiaz Ali, Najma; Brohi, Imtiaz Ali (Science Publishing Corporation Inc, 2018)
The Kingdome of Saudi Arabia (KSA) and its growth objective is to be a major player in the global economy and moving toward a knowledge-based economy. To achieve its objectives, the private sector in various fields in KSA needs to be in line with country’s ambitious goal; Knowledge Management (KM) handling and readiness for the foreseen customer demand need to be in line with goals. This study presents a critical review to evaluate existing KM practice in the private sector in Kingdom of Saudi Arabia (KSA) to see the readiness of this sector to play an integral role of knowledge-based economy and support nation’s growth strategy. The paper will examine current states in term of how knowledge management is practiced in the country. This paper addressed various aspects of knowledge management ranges from the need of implementing knowledge management systems to the added value by deploying such systems. In addition, the review was discuss if the private sector is heading in the right direction, and coherent with KSA strategic goal by examining a sample of four major firms in private sector. The outcome of the sample reflected that the private sector is harmonized with KSA objective.